Pengelolaan Dana Bantuan Operasional Sekolah di SDN Papringan 02 Kaliwungu Semarang - Melati, Tiwik; , Drs. H. Muhroji., S.E., M.Si., M.Pd (2017)
This study aims to describe the management of school operational funds (BOS) at SDN 02 Papringan Kaliwungu Semarang. This research is a qualitative case study research design. The technique of collecting data using interviews, observation and documentation, while the data analysis technique consists of data reduction, data presentation and verification. Examination of the validity of the data using triangulation sources. Based on the research findings can be concluded that a) Planning RKAS SDN Papringan 02 Kaliwungu Semarang prepared by the school's budget team by involving all teachers and employees. Budget, sorted by activity / needs of teachers and employees. The plan, which has been arranged and then communicated to the School Committee for consideration. b) The implementation of BOS BOS Fund distribution begins. BOS funds collected every quarter. Spend goods / services implemented by all parties of the schools by applying the principles of effective and efficient. c) SDN Papringan 02 Kaliwungu Semarang BOS Fund Management reported to the District Education Office, Provincial and Central. School RKAS publish detailed summary of funds received and expenditures per fiscal year on the bulletin board. It also informs the use of BOS funds to parents by providing a sheet of paper when a meeting is held.